Further comments on the use of interview-based data for species distribution studies: a reply to Petracca & Frair - Caruso, Nicolás (2017)
In their letter, Petracca & Frair (2016) detail several methodologicalconsiderations in our examination of whether interview-based surveys produce unreliable results (Caruso et al., 2016). We thank them for pointing out these issues and, by doing so, helping to strengthen our main point.